ANALISA PERBANDINGAN KINERJA PERANGKAT WIRELESS STANDART “IEEE 802.11G D-Link DSL 2640 B DENGAN TP-Link TD-W8101G “STUDY KASUS UNTUK HOTSPOT AREA RT.04 / RW.XI PRAMBANAN TIMUR KELURAHAN KALIPANCUR” (Information Technology and Telematics, 2012)
wireless network is one of [the] best alternative in builds a computer network practise. in this testing, author does testing towards two wares wireless standart IEEE 802.11g Tp-link td-w8101g with D- link dsl 2640b, both a ware 3-in-1 that unite high- speed function dsl modem, wireless-g, will support adsl2 / 2+ to will give performance higher (until 24mbps) in ware testing wireless this will discuss about performance measurement and parameter that discussed scanning signal, speed downloads upload and stability. based on from analysis result and watchfulness that done so produced a conclusion  that  give  solution  and  suggestion  in ware election acces point correct to study case hotspot at area prambanan east rt. 04/rw. xi sub- district kalipancur. keyword: Wlan, IEEE 802.11 g, Access point. Inssider